Effect of irrigation regime and nitrogen fertilization on bulb yield and water use of onion (Allium cepa) - RANA, D S; SHARMA, R P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the spring seasons of 1991 and 1992 at New Delhi to study the effect of irrigation regime and nitrogen on water use and yield of 'Pusa Madhavi' onion (Allium cepa L.). Irrigations at 1.25 irrigation water: cumulative pan-evaporation (IW : CPE) ratio (14-16 irrigations) and I.75IW: CPE ratio (19-21 irrigations) were at par, giving 69.6 and 72.8% higher bulb yield respectivelythan 0.75 IW : CPE ratio (9-11 irrigations). The seasonal consumptive use was 500, 636 and 784 mm with irrigation at 0.75, 1.25 and 1.75IW: CPE ratio respectively. The water-use efficiency was maximum (50.3 kg/ha/mm) at 1.25 IW : CPE ratio. N application up to 120 kg/ha gave significantly higher dry matter/bulb. 100-bulb weight, bulb diameter and bulb yield than 60kg/ha. The net return/Re investment on Nwas Rs 12.4 at the optimum level of 131.4 kg N/ha. Increase in N level from 0 to 120 kg/ha increased the consumptive use and water-use efficiency from 560 to 628 mm and 38.1 to 52.1 kg/ha/mm respectively.